Przeprowadzenie dowodów przez sąd z urzędu - Rzewuska, Magdalena (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The paper discusses the problem of taking evidence ex officio by the court. This topic was selected due to controversies it arouses both in the doctrine and judicature. This work attempts to provide answers to the four important questions: is admitting evidence ex officio by the court in compliance with constitutional principles?; is it restricted only to specific circumstances?; is the duty to present evidence by the court always left to its discretion?; should the court allow evidence ex officio in the event the parties are represented by professional legal representatives?